Tax Sparing, FDI, and Foreign Aid: Evidence from Territorial Tax Reforms - Céline Azémar; Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2016)
The governments of many developing countries seek to attract inbound foreign direct investment (FDI) through the use of tax incentives for multinational corporations (MNCs). The effectiveness of these tax incentives depends crucially on MNCs' residence country tax regime, especially where the residence country imposes worldwide taxation on foreign income. Tax sparing provisions are included in many bilateral tax treaties to prevent host country tax incentives being nullified by residence country taxation. We analyse the impact of tax sparing provisions using panel data on bilateral FDI stocks from 23 OECD countries in 113 developing and transition economies over the period 2002-2012, coding tax sparing provisions in all bilateral tax treaties among these countries. We find that tax sparing agreements are associated with 30 percent to 123 percent higher FDI. The estimated effect is concentrated in the year that tax sparing comes into force and the subsequent years, with no effects in prior years, and is thus consistent with a causal interpretation. Four countries - Norway in 2004, and the U.K., Japan, and New Zealand in 2009 - enacted tax reforms that moved them from worldwide to territorial taxation, potentially changing the value of their preexisting tax sparing agreements. However, there is no detectable effect of these reforms on bilateral FDI in tax sparing countries, relative to nonsparing countries. These results are consistent with tax sparing being an important determinant of FDI in developing countries for MNCs from both worldwide and territorial home countries. We also find that these territorial reforms are associated with increases in certain forms of bilateral foreign aid from residence countries to sparing countries, relative to nonsparing countries. This suggests that tax sparing and foreign aid may function as substitutes.
Keywords: H25; F21; F35; 330; FDI; international tax; development; foreign aid; tax sparing